2014
DOI: 10.1093/jxb/eru255
|View full text |Cite
|
Sign up to set email alerts
|

PEG-mediated osmotic stress induces premature differentiation of the root apical meristem and outgrowth of lateral roots in wheat

Abstract: SummaryPEG-mediated osmotic stress induces premature differentiation of the root apical meristem, which in turn leads to outgrowth of lateral roots and improved tolerance to water stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 33 publications
11
62
0
3
Order By: Relevance
“…Six day-old mutants defective in ABA biosynthesis (aba2-1) and the signaling pathway (the triple mutant of ABA receptors pyr1/pyl1pyl4) were subjected to 5% PEG 8000 simulated water stress as described previously. 3 As shown in, Fig. 2A root tips of the aba2-1 and pyr1/ pyl1pyl4 mutants were morphologically comparable to the wild type under normal conditions.…”
Section: Aba and Signaling Pathway Affect Ram Premature Differentiatimentioning
confidence: 59%
See 2 more Smart Citations
“…Six day-old mutants defective in ABA biosynthesis (aba2-1) and the signaling pathway (the triple mutant of ABA receptors pyr1/pyl1pyl4) were subjected to 5% PEG 8000 simulated water stress as described previously. 3 As shown in, Fig. 2A root tips of the aba2-1 and pyr1/ pyl1pyl4 mutants were morphologically comparable to the wild type under normal conditions.…”
Section: Aba and Signaling Pathway Affect Ram Premature Differentiatimentioning
confidence: 59%
“…2 Recently, we reported that under mild and moderate water stresses, plant primary roots undergo root tip swelling and RAM premature differentiation resulting in cessation of the primary root growth. 3 We demonstrated that the RAM premature differentiation of primary roots and subsequent lateral formation are directly correlated to plant stress tolerance. Importantly, we provide evidence that the RAM premature differentiation and remodeling of root system architecture induced by mild and moderate water stresses simulated by PEG8000 is a conserved adaptive mechanism that is well adopted by various plants to cope with water stress.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Extensive research efforts over the last five decades revealed physiological mechanisms relevant to osmotic stress response of crop plants [8][9][10][11][12][13]. Awareness related to root morphology of annual crop plants, such as wheat, barley, or perennial forage grasses under limited water supply, has developed within the last 20 years [14][15][16][17][18][19][20][21][22][23]. However, little awareness has been created as to how root hairs get modified, and are possibly associated with crop yield under different levels of osmotic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Lower concentrations of NaCl reduced root growth, which was also reflected in the reduction of the size of the root meristem (Hanif andDavies 1998, Zadeh 2007). Recently, a reduction in root meristem size was also reported for wheat under PEG-mediated osmotic stress (Ji et al 2014). However, the mechanism by which the stress affects the meristem length is not fully understood.…”
Section: Introductionmentioning
confidence: 99%